2014
DOI: 10.1103/physreva.89.013828
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium states and chaos in an oscillating double-well potential

Abstract: We investigate numerically parametrically driven coupled nonlinear Schrödinger equations modelling the dynamics of coupled wavefields in a periodically oscillating double-well potential. The equations describe among other things two coupled periodically-curved optical waveguides with Kerr nonlinearity or horizontally shaken Bose-Einstein condensates in a double-well magnetic trap. In particular, we study the persistence of equilibrium states of the undriven system due to the presence of the parametric drive. U… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…where the effective parameters are tunneling energy k 0 (15), difference of energies between the wells ∆E (18) and self-interaction energy Λ (19). Using Lagrangian For the center condensate, the equations of motion of ξ and w are obtained as…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…where the effective parameters are tunneling energy k 0 (15), difference of energies between the wells ∆E (18) and self-interaction energy Λ (19). Using Lagrangian For the center condensate, the equations of motion of ξ and w are obtained as…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, several experiments have successfully observed coherence oscillations through quantum tunneling of atoms between the condensates trapped in a double well potential [12][13][14], whereas similar phenomena were also seen from attractive to repulsive atomic interactions by experimentally changing atomic scattering lengths through Feshbach resonances [15]. In addition to the regular coherent oscillations mentioned above, the studies on the possibility of the appearance of chaotic motions, by applying an externally time-dependent trap potential, are also a fascinating task with findings that deserve further experimental justification [16][17][18][19].…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…[20] Undoubtedly, the superfluids can exert significant influence on BECs, and may even result in chaotic behaviors in the system. It has been reported that for some specific parameters and initial/boundary conditions, spatial chaos [23][24][25][26][27][28] and dynamical chaos [29][30][31][32][33][34][35][36][37][38][39][40][41] can appear in BECs. Due to the diversity of the configurations of BEC systems, there are still open problems to be considered.…”
Section: Introductionmentioning
confidence: 99%